Azad Kashmir Reflections in Vikram A. Chandra's The Srinagar Conspiracy. (November 2022) - Karmakar, Goutam
The contested identity of Kashmir and Kashmiris and their intrinsic pain of hoping for freedom [ Azadi ] have found expression through The Srinagar Conspiracy, a novel by Vikram A. Chandra (2000). The article highlights how, through the fractured friendship between a Muslim and a Kashmiri Pandit boy, Chandra traces the upsurge of militant insurgency in Kashmir in the late 1980s and 1990s. The article also examines how the changing dynamics of identity were manipulated by the politics of ethnic and religious nationalism in Kashmir, leading to the 1989 insurgency and its drastic implications. The article also shows how the ethos of Kashmiriyat has been compromised, while the call for azad [free] Kashmir has remained an unrealised dream.